György Lukács’ Thought About Cinema. A Relational Aesthetics - Navarro Fuentes, Carlos Alberto (2025)
The central objective of this essay is to show the aesthetic-cinematographic thinking of György Lukacs. The above is achieved based on texts on the subject in his youth, where he exposes his ideas regarding the pros and cons that he observes in this new art and its potential development, as well as its uncertain scope based on technical development and the relationship it maintains with other arts such as theater, photography and painting, on the one hand; and, reviewing the most mature texts of the Hungarian thinker, where he suggests a series of critical-epistemological concepts to think more scientifically about the aesthetic, sociological, political and technical nature of cinema, on the other hand. It is concluded that Lukacs’s aesthetic theory, in general; and, the specific theory on cinema, continues to have significant importance for understanding and studying cinema as an artistic expression.